2015
DOI: 10.1007/s00590-015-1651-0
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of depression and its influence on surgical outcomes of lumbar degenerative diseases

Abstract: Most patients with depression in the preoperative recover within 1 year postoperatively. Responsiveness of depression is associated with surgical outcomes. The presence of depression after the surgical treatment, independent of when it starts, had a major negative impact on prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…[39] There is a lack of studies focusing on surgically treated LSS patients, especially with longer follow-ups than 5 years. A one-year follow-up study by Falavigna et al [25] suggested that since depression in the postoperative period might have worse effects on the clinical outcome than in the preoperative period, the assessment of depressive symptoms during the postoperative period is more important. These findings underline the need to evaluate depressive symptoms and other possible psychological distress also during postoperative rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39] There is a lack of studies focusing on surgically treated LSS patients, especially with longer follow-ups than 5 years. A one-year follow-up study by Falavigna et al [25] suggested that since depression in the postoperative period might have worse effects on the clinical outcome than in the preoperative period, the assessment of depressive symptoms during the postoperative period is more important. These findings underline the need to evaluate depressive symptoms and other possible psychological distress also during postoperative rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] On the other hand, depression and psychological well-being can improve after decompressive surgery, and those who have experienced psychological distress also gain benefits from surgery. [16,25,26] So far, the longest follow-up period in which the association between depressive symptoms and the surgical outcome has been evaluated in LSS patients has been five years. [21] The effects of depressive symptoms on the surgical outcome in LSS patients has not studied in a 10-year follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…spine disease is known to bias the subjective, PROM-based outcome assessment [39][40][41] . One of the hopes of objective outcome measures is to provide an accurate determination of functional outcome, irrespective of the mental health condition 42 .…”
Section: Assessment In Patients With Depression the Mental Health Comentioning
confidence: 99%
“…However, Blozik et al,29 who studied the effects of anxiety and depression in patients suffering from cervical pain, reported a significant correlation between the intensity of neck pain and depression. However, a recent study by Falaviga et al30 has shown that patients suffering from chronic depression, even without pain, have a worse response to surgery compared with patients without depression or pain.…”
Section: Discussionmentioning
confidence: 99%